Systemic antibiotics in periodontal therapy - Garcia, Ma. Celina U.
Current concepts in the management of periodontal diseases are rooted in the etiology and pathogenesis of such diseases. Hence, conventional therapy consists of the mechanical removal of the supra and subgingival biofilm from tooth surfaces, in order to control inflammation and arrest the progression of periodontal tissue destruction. Majority of periodontitis cases respond well to scaling and root planing, improved oral hygiene and supportive periodontal treatment. However, certain subsets of patients do not respond well to mechanical therapy alone, due to persistence or regrowth of periodontal pathogens in treated sites. In these patients who do not respond adequately to conventional mechanical debridement, additional antimicrobial therapy may therefore be indicated, in order to improve clinical outcome. Antibiotics may be administered either systematically or locally into the pocket. This paper will discuss only the use of systemic antibiotics in periodontal therapy.
Keywords: Periodontics